Life skills training to promote health and well-being at school: an evaluation. (20th October 2021) - Cattaneo, C; Giovannelli, I; De Nigris, N; Russo, E; Buoncristiano, M; Rosa, B; Ripoli, G; Parenti, I; Indorato, E; ,
Abstract: Background: In educational settings, health promotion refers to a whole-school approach to help individuals realize their potential, cope with the everyday stresses of life, work productively and fruitfully, and contribute to their community. In these regards, it is essential to enhance a vast repertoire of knowledge, skills, attitudes, and values, a narrower set of psychosocial skills (Life Skills - LS). The Local Health Unit of Palermo, the Centre of Training and the National Institute of Health (ISS) developed the project "Life Skills and resilience: effective strategies to promote health at school". Objectives: The project's general aim was to provide headteachers and teachers with methodologies and tools to develop and promote LS in educational settings. Through the participatory approach, training was structured in 5 modules of 16 hours each. The training activities began in October 2019 and ended online due to the Covid-19 emergency in July 2020. The evaluation plan provides the assessment of learning, satisfaction, monitoring and assessment of attitudes and behaviours using a validated questionnaire. The aim was to identify improvements in relationships inside and outside the school context and increase self-efficacy and job satisfaction among teachers. Data analysis is currently being processed. Results: 169 Teachers, 12 Healthcare workers attended the training. The preliminary results show that: i. there is an improvement in relationships between colleagues, students and parents; ii. there is a slight improvement in the perceived self-efficacy in managing negative emotions; iii. there is an improvement in the personal and collective effectiveness perceived in the school environment and job satisfaction. Conclusions: The project was designed for implementing sustainable interventions. The advent of COVID-19 has allowed further reflection on the usefulness of this approach for promoting resilience and protective factors and managing the consequences of the pandemic. Key messages: The training improved personal and professional skills on design and methods to apply LS. The use of qualitative/quantitative assessment made it possible to illustrate the entire training process.